Factors Associated with Insomnia Symptoms among Elderly in Primary Care Unit - Rattanaphongset, Phanida; Bosittipichet, Tatree; Nakawiro, Pakkawee (Journal of Preventive Medicine Association of Thailand, 2021)
Insomnia is the most common sleep disorder of any age. Most of older adults experience symptoms of insomnia and this can be attributed to age-related sleep change pattern. One-third of elderly patients reported insomnia symptoms.(1) By understanding these factors, it may be possible to resolve their problems and also minimized the long-term complication from insomnia. Moreover insomnia may also be one of early signs in many chronic illness conditions including depression. Despites growing study about factors associate with insomnia but not clearly understand in some factors. The objective of this research was to study the factors associated with insomnia symptoms in elderly. In cross-sectional survey conducted from September to December 2020, 300 elderly who aged over 60 were included with 150 persons who experienced insomnia and 150 non-insomnia person equally. Data were collected by a questionnaire which contained general information, factors associated with insomnia, Insomnia severity index, Thai Geriatric Depression Scale (TGDS) and stress test (5ST). Data analysis using descriptive statistics has included percentage, average, standard deviation and analytic statistics such as Independent t-test, Chi square test. The results were analyzed by Binary logistic regression to delineate multivariate analysis. The finding indicates that most of elderly who experienced insomnia were female (76.0%), 70.3 ±6.7 years old on average, married (60.0%) and had inadequate income (59.0%). The factors associated with insomnia in elderly included female, inadequate income, depression, and moderate/high/severe stress level. Many factors are associated with insomnia among the elderly. Screening and observing such factors will allow detection and diagnosis at the early stages in order to decrease a long-term complication.